(untitled) (Research, Society and Development, 2025)
The aim of this study was to investigate and compare diaphragmatic thickness (DE) and pulmonary function in postoperative (PO) patients after upper abdominal surgery compared to healthy individuals. This is a comparative cross-sectional pilot study carried out in a university hospital, with 30 participants divided into two groups: 15 patients in the postoperative period of upper abdominal surgery and 15 healthy individuals. PE was assessed by bedside ultrasound and lung function by spirometry, considering forced vital capacity (FVC), diaphragmatic fraction and proportion of muscle activation. The results showed that PE during inspiration was significantly lower in the PO group (p 0,0417). FVC was also lower in surgical patients (p 0,0012), impairing lung function. However, diaphragm muscle activation was higher in the PO group (p 0,0448), providing compensation for the loss of muscle thickness. The diaphragmatic fraction showed no statistically significant difference between the groups. It is concluded that after upper abdominal surgery there is a greater recruitment of motor units as a strategy to maintain ventilation. Ultrasound proved to be a useful tool for assessing diaphragmatic dysfunction in the postoperative period and can help monitor these patients.